A CBCT Based Assessment of Canine Eruption and Development Following Alveolar Bone Grafting in Patients Born With Unilateral Cleft lip and/or Palate. (April 2023) - Kadi, Hasan; Jacobs, Reinhilde; Shujaat, Sohaib; Lemberger, Mathias; Benchimol, Daniel; Karsten, Agneta; Pegelow, Marie
Objectives : To three-dimensionally assess and visualize the eruption path and development of the maxillary canine following alveolar bone grafting in patients born with cleft lip and palate. A further objective of this analysis was to assess how the presence of the lateral incisor impacts the eruption path of the canine. Design : Observational follow-up study. Setting : Stockholm Craniofacial Team, Karolinska University Hospital, Sweden. Patients : Thirty children born with non-syndromic unilateral cleft lip with or without palate were consecutively included. Intervention : CBCT scans of the maxilla were taken six months before and six months after the alveolar bone-grafting surgery for each patient. Main Outcome Measures : Canine eruption (angulation and vertical movement) and canine development (length and volume). Results : There was a significant difference pre- and post-operatively of the canine angulation between the cleft and non-cleft sides. The mean angulation on the cleft side was 14.7° (SD = 11.1°) while on the non-cleft side, it was 4.9° (SD = 9.2°). No significant differences were noted between cleft-side and non-cleft side canines in terms of amount of vertical eruption and volumetric development. Absence of the lateral incisor did not significantly contribute to either canine angulation or its vertical eruption on the cleft-side. Conclusion : Higher angulation of the canine on the cleft side indicates a higher risk of future canine impaction. Presence or absence of the lateral incisor did not significantly affect canine angulation or its vertical eruption. Increased age and children born with total cleft lip and palate imply a higher risk of angulated canines on the cleft side.